Una mirada a los fundamentos biológicos de la educación desde la teoría de Santiago - Méndez Santos, Dr. Isidro E.; Carvajal Hernández, Dra. Bárbara M. (Transformación, 2024)
Methods: Theoretical methods such as analytical-synthetic, inductive-deductive, historical-logical and ascension from the abstract to the concrete were used to assess information from the bibliographic sources consulted. Empirical techniques connected to document analysis allows to collect the best university teaching experiences in leading the study of these topics for more than 30. Results: The importance of the category system of the theory of Santiago (autopoiesis, structural coupling, cognition, behavior, nervous system, behavioral coordination, communication, cultural behavior, language, self-consciousness and reflection, among others), is highlighted to unveil the essence of the subjects involved in the educational process and the qualities that make their education possible. Conclusions: The theory of Santiago provides theoretical assumptions that help to explain a large part of the biological foundation that underlies education. Not taking them into account would mean ignoring the living essence of the participants in the process and would constitute, among other things, an ontological, gnoseological and methodological error.